Protocol for a process evaluation: face-to-face physiotherapy compared with a supported home exercise programme for the management of musculoskeletal conditions: the REFORM trial. Issue 7 (5th July 2022) - Withers, Hannah G; Liu, Hueiming; Glinsky, Joanne V; Chu, Jackie; Jennings, Matthew D; Hayes, Alison J; Starkey, Ian J; Palmer, Blake A; Szymanek, Lukas; Cruwys, Jackson J; Wong, David; Duong, Kitty; et al.
Abstract : Introduction: The REFORM (REhabilitation FOR Musculoskeletal conditions) trial is a non-inferiority randomised controlled trial (n=210) designed to determine whether a supported home exercise programme is as good or better than a course of face-to-face physiotherapy for the management of some musculoskeletal conditions. The trial is currently being conducted across Sydney government hospitals in Australia. This process evaluation will run alongside the REFORM trial. It combines qualitative and quantitative data to help explain the trial results and determine the feasibility of rolling out supported home exercise programmes in settings similar to the REFORM trial. Methods and analysis: Two theoretical frameworks underpin our process evaluation methodology: the Realist framework (context, mechanism, outcomes) considers the causal assumptions as to why a supported home exercise programme may be as good or better than face-to-face physiotherapy in terms of the context, mechanisms and outcomes of the trial. The RE-AIM framework describes the Reach, Effectiveness, Adoption, Implementation and Maintenance of the intervention. These two frameworks will be broadly used to guide this process evaluation using a mixed-methods approach. For example, qualitative data will be derived from interviews with patients, healthcare professionals and stakeholders, and quantitative data will be collected to determine the cost and feasibility of providing supported home exercise programmes. These data will be analysed iteratively before the analysis of the trial results and will be triangulated with the results of the primary and secondary outcomes. Ethics and dissemination: This trial will be conducted in accordance with the National Health and Medical Research Council National Statement on Ethical Conduct in Human Research (2018) and the Note for Good Clinical Practice (CPMP/ICH-135/95). Ethical approval was obtained on 17 March 2017 from the Northern Sydney Local Health District Human Research Ethics Committee (trial number: HREC/16HAWKE/431-RESP/16/287) with an amendment for the process evaluation approved on 4 February 2020. The results of the process evaluation will be disseminated through publications in peer-reviewed journals and presentations at scientific conferences. Trial registration number: ACTRN12619000065190.